Study on characteristics behavior of developing nozzle for aerosol spray - Ramlan, Aslinda (2012)
A new generation of aerosol technology are expand rapidly where the research and development are focused on the analysis of propellants, packaging and ingredients to make the aerosol has a high performance product. However, there are a few main problems with pressurised aerosol spray, which are the production of VOC and the quality of spraying process. Therefore, in this study the development of an internal nozzle has been investigated to analyse the characterictics of spray by using CFD simulation. The analysis is focused on various pressure supply up to 9bar, where the n-butane and water are applied as a liquid phases material. The simulation is done based on two types of selected nozzle design. The result shows that, the values of velocity, TKE and Reynolds Number for both liquid phases are increase when the pressure supply increased. It was observed that, when comparing the two type of nozzle design, it shown that the value of velocity and Reynolds number is relatively similar for both liquid phases, while the TKE value is more difference due to the material properties and nozzle design. Therefore, the use of water is acceptable as an alternative to substitute the n-butane liquid phase in producing an aerosol spray product.